Corrosion Behavior of Aspergillus niger on 7075 Aluminum Alloy and the Inhibition Effect of Zinc Pyrithione Biocide. Issue 8 (19th April 2019) - Wang, Junlei; Li, Chenjing; Zhang, Xinxin; Asif, Muhammad; Zhang, Tiansui; Hou, Baoshan; Li, Yanyan; Xia, Wu; Wang, Haitao; Liu, Hongfang
Abstract : The corrosion induced by Aspergillus niger on 7075 aluminum alloy and a protection method by adding zinc pyrithione (ZPT) biocide have been studied through systematic experiments. From the third day, A. niger depicted a strong metabolism, leading to a serious local and uniform corrosion owing to the presence of acidic metabolites. The inhibition efficiency based on 14-day weight loss reached up to 98% when 100 mg/L ZPT biocide was added, corresponding to the results of surface morphology analysis and electrochemical data. The above results showed that the ZPT has a good inhibition effect on the corrosion induced by A. niger .